PENERAPAN MEDIA PEMBELAJARAN BERBASIS IT TERHADAP ANAK BERKEBUTUHAN KHUSUS DI LABSCHOOL UNNES - Azizah, Farinka Nurrahmah; Nisak, Masfufatun; Wildan, Mukhammad Khouf; Widyastuti, Noviana (Institut Daarul Qur'an Jakarta, Indonesia, 2024)
The implementation of IT-based learning media for children with special needs at Labschool UNNES, particularly in English language education, is the focus of this research. The research method used is qualitative descriptive, employing interviews, observations, and document studies as data collection techniques. The objective is to describe how IT-based learning media, specifically the Wordwall application, is applied in the learning process of Grade 3B. Direct observations indicate that the use of Wordwall provides a positive stimulus for active student participation, including for children with disorders such as OCD and autism. Teachers utilize this media by displaying interactive games on a projector screen following an initial icebreaking session, aimed at preparing students to understand English grammar topics such as past tense. During this process, students are encouraged to participate in answering questions through games tailored to their needs. The findings show that this approach is effective in enhancing student engagement in learning, including for students with special needs, by providing additional assistance such as clues to facilitate comprehension of the material. The positive response from teachers towards the use of Wordwall indicates its adaptability to students' needs, including those requiring more specialized learning approaches. Labschool UNNES, as an inclusive school, demonstrates its commitment to integrating information technology early on, starting from Grade 1, with the goal of ensuring students master and effectively utilize technology. This aligns with modern educational policies recognizing the importance of technology in supporting inclusive and enjoyable learning processes. In conclusion, the implementation of IT-based media such as Wordwall in English language education at SD Labschool UNNES, especially for children with special needs, can be effectively conducted. Special needs students are able to comprehend and actively participate in learning through engaging and supportive media. Recommendations include the need to enhance the use of information technology in primary education to improve learning effectiveness and prepare students for future technological challenges.